2011
DOI: 10.1113/jphysiol.2010.202820
|View full text |Cite
|
Sign up to set email alerts
|

Loss of visceral pain following colorectal distension in an endothelin‐3 deficient mouse model of Hirschsprung's disease

Abstract: Non-technical summary The endothelin-3 (ET-3) gene is essential for the development of the enteric nervous system in the gastrointestinal tract of mammals, including humans and mice. Loss of the ET-3 gene leads to the formation of an aganglionic colorectum and impaired bowel function. Endogenous endothelin peptides and their receptors also play a major role in nociception in a variety of organs and species, including humans. However, whether nociception is altered in the aganglionic region of the colorectum is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 50 publications
1
53
0
Order By: Relevance
“…41 Especially for EDN3, a reduction in spinal sensory innervation of the rectum was reported in mice with disruption of Edn3 gene expression. 42 In line with this, this study also showed that perturbation of Hoxb5 function in NCC of mice causes multiple neurological phenotypes and hypopigmentation, resembling some of the phenotypes of syndromic HSCR. Nevertheless, the causal relationship between abnormal HOXB5 function and HSCR in human deserves further investigation, in particular, the identification of a dominant-negative type of HOXB5 mutation in these patients.…”
Section: Discussionsupporting
confidence: 81%
“…41 Especially for EDN3, a reduction in spinal sensory innervation of the rectum was reported in mice with disruption of Edn3 gene expression. 42 In line with this, this study also showed that perturbation of Hoxb5 function in NCC of mice causes multiple neurological phenotypes and hypopigmentation, resembling some of the phenotypes of syndromic HSCR. Nevertheless, the causal relationship between abnormal HOXB5 function and HSCR in human deserves further investigation, in particular, the identification of a dominant-negative type of HOXB5 mutation in these patients.…”
Section: Discussionsupporting
confidence: 81%
“…This profile suggests that their peripheral terminals may be rectal IGLEs (33,34,65). They fire to small amounts of stretch and continue to encode without saturating to distensions into the noxious range (64). Consistent with HF afferents, rectal IGLEs are present in the murine colorectum (55).…”
Section: Discussionmentioning
confidence: 62%
“…Electrophysiologically, they are typically silent at rest, but are powerfully activated by distension, with instantaneous firing frequencies up to 50 Hz. 42 The degree of distension at which their response saturates has not been determined, but they encode stretch over a wide dynamic range, into the noxious extremes 146 . They are activated by contraction of both the longitudinal and circular muscle layers, possibly via compressive forces acting on myenteric ganglia.…”
Section: Sacral Spinal Intraganglionic Laminar Mechanoreceptorsmentioning
confidence: 99%
“…Evidence suggests that low-threshold, wide-dynamic range lumbosacral mechanoreceptors from the colorectum, which dominate pelvic nerve responses to rectal distension, are likely to be responsible for activation of pain pathways. 146 These mechanoreceptors include rIGLES and rectal muscularmucosal endings. Interestingly, sensation evoked by slow ramp distension in the human rec-tum was reduced by luminal application of the local anaesthetic, lidocaine, which suggests a possible role for muscular-mucosal afferents with endings close to the mucosal surface.…”
Section: Extrinsic Afferent Pathways and Sensationmentioning
confidence: 99%